SOCIAL REHABILITATION MODEL FOR ADDICT PRISONERS WITH COGNITIVE BEHAVIOR THERAPY APPROACH - Rahmadila, Hanifah; Equatora, Muhammad Ali (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Efforts to eradicate narcotics in Indonesia do not only depend on strict legal regulations against narcotics dealers and dealers, but also involve recovery strategies for addicts, abusers, and victims of narcotics abuse through the implementation of rehabilitation programs. Cooperation between Correctional Institutions and various related agencies, including health institutions and social institutions, is strengthened to design a comprehensive approach. The author uses a descriptive qualitative research design. The results of this research are the implementation of a social rehabilitation model for addicted convicts using a CBT approach in the Class IIA Palembang Women's Prison, a program that has been implemented to fulfill prisoners' rights to receive rehabilitation while serving their criminal term. Drug rehabilitation using the CBT approach is one form of rehabilitation in the Palembang Class IIA Women's Prison where the results of this rehabilitation can reduce addiction and recidivism rates in the Palembang Class IIA Women's Prison itself. Keywords: Narcotics; Cognitive Behavior Therapy; Correctional Institutions; Rehabilitation